Modelling pre-hispanic settlement patterns in alto de toche, colombia (2024)
The enhancement of the archaeological terraces on the Alto de Toche and the Wax Palm forest is unprecedented. The Toche region in Colombia contains an outstanding anthropised ecosystems presence (8000 BP), characterised by complex inherited cultural patterns, according to the evidences on the eastern margin of the Andes Central Cordillera. The research focused on i) the cultural landscape of the Premontane and Montane Cloud Forests of the Alto de Toche, built by the Toches; ii) its high-altitude settlements, interpreted as a strategy of ecological knowledge, deeply linked to their symbolic understanding of the landscape. Fieldwork in three sets of tambos (terraces for habitational settlements) in La Carbonera, Gallego, and Las Cruces sites was analysed using remote sensing, drone digital photogrammetry, and on-site data. Their interpretation projected a settlement pattern; a typological-topological tambos classification inferred its possible functions such as sighting, funerary, and dwelling, from 2600 MASL to biggest sites at 3000 MASL, related to the sun-moon proximity presumed for gatherings. The authors conclude that the patterns respond to a territorial understanding of its resources and the vertical exploitation of the agricultural thermal floors and micro-watersheds, associated with the east-west solar illumination over both sides of the Tochecito River basin; linked with the transit between ridges and steep slopes, through the network of pathways that originated the Quindío Trail. Data were projected crossing field-data photogrammetry with GIS spatial analysis; this resulted in a terrain model that reconstructs a geoarchaeological landscape composed of massive systems of tambos. Thirty-seven new sites were classified, twenty of them above 2800 MASL. The resulting terrain model facilitates a non-invasive previous prospection for fieldwork planning and a more feasible knowledge of accessibility, due to on-site transit difficulties (steep slopes and very unstable soil due to cattle ranching). Finally, the terrain model was uploaded in an easy-to-access ArcGIS-online web application for sharing with community stakeholders and visiting scientists.